2011
DOI: 10.1029/2010ja016323
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale PIC simulation of double layers and electron holes affecting parallel and transverse accelerations of electrons and ions

Abstract: [1] We study the dynamical behavior of potential structures in the auroral upward current region. The study is based on a large two-dimensional particle-in-cell simulation. A double layer (DL) forms in the auroral potential structure in the counterstreaming expansion of cold and hot plasmas from bottom (ionospheric side) and top (magnetospheric side), respectively. Transversely nonuniform converging perpendicular electric field drives the plasma from the top, generating V-shaped potential structure within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…Recently, Singh et al . [] find that multiple dynamically evolving DLs could be created in their particle‐in‐cell simulations, which is consistent with our observation in the period E3.…”
Section: Observation and Analysissupporting
confidence: 90%
“…Recently, Singh et al . [] find that multiple dynamically evolving DLs could be created in their particle‐in‐cell simulations, which is consistent with our observation in the period E3.…”
Section: Observation and Analysissupporting
confidence: 90%
“…In this condition, strong DLs can be generated at the reconnection site. These simulation results have been confirmed by the cluster observations published by Vaivads et al (2004).…”
Section: Simulation Resultssupporting
confidence: 85%
“… Farrell et al [1998] showed electrostatic instabilities in the wake with 1‐D PIC simulations, although they did not further address the nature of the electrostatic instabilities. Birch and Chapman [2001a, 2001b, 2002] observed nonlinear electrostatic waves, namely, electron phase space holes [ Roberts and Berk , 1967; Singh et al , 2011], in 1‐D and 2‐D PIC simulations of the wake.…”
Section: Discussion and Summarymentioning
confidence: 99%